Answer:
![YA=7x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xx941djtbrobbmje90kvdotxxrtizv6kg9.png)
Explanation:
You know that "Z" is the midpoint of "YA". This means the following:
![YZ+ZA=YA](https://img.qammunity.org/2020/formulas/mathematics/middle-school/thrckiiphahc2861ybnxqkjqvy5sszxr9w.png)
Now, you know that the expression for "YZ" is:
![YZ = x + 12](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rqo3husy5559cjvy9sm7po56g0e2vtcqea.png)
And the given expression for "ZA" is:
![ZA = 6x - 13](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2gg8bxtoufq5u3re8zscodk48l1zpm1vdl.png)
Knowing these expressions, you can substitute them into
, as following:
![( x + 12)+(6x - 13)=YA](https://img.qammunity.org/2020/formulas/mathematics/middle-school/su7tl5txyp9azn1xncxpo39xmzxs3ncyyl.png)
Finally, you must add these expressions in order to get "YA".
Therefore, this is:
![x + 12+6x - 13=YA\\\\7x-1=YA\\\\YA=7x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/jr3ok80rj5hqqgx4yw8y6mfn50n63ls0e6.png)